Thermal Variability in the Martian Upper Atmosphere within the Crustal Magnetic Field Region Induced by Gravity Wave Dissipation Due to Ion-drag Effect - Xing Wang; Xiaojun Xu; Jun Cui; Siqi Yi; Hao Gu; Zilu Zhou; Hengyan Man; Lei Luo; Peishan He; Pu Yang (The Astronomical Journal)
Mars Atmosphere and Volatile Evolution detected a significant temperature increase of approximately 20–40 K in the upper atmosphere within the strong crustal magnetic field (CF) region during two deep dip campaigns. Previous studies were unable to fully explain this thermal variation. Atmospheric gravity waves are an underlying mechanism, attributed to the ion-drag effect. During this effect process, the collisions between neutral particles and ions transfer wave momentum along the magnetic field lines, and lead to wave dissipation and energy release to heat or cool the background atmosphere. We developed a one-dimensional linear wave model to describe the effect of ion-drag on wave propagation and dissipation in the Martian upper atmosphere. Our results show that the ion-drag effect influences wave propagation primarily above 160 km in the CF region and around 200 km in the noncrustal magnetic field (NCF) region. The total wave energy flux driven by the ion-drag effect in the CF region is approximately 10 ^8 eV cm ^−2 s ^−1 , with heating rates of 10–60 K per sol and cooling rates up to 40 K per sol above 155 km. Wave-driven temperature enhancements in the CF region due to the ion-drag effect are a few Kelvins higher than in the NCF regions, though still smaller than the observed 20–40 K. Additional wave processes, including wave breaking and multiwave dissipation, may contribute to the observed thermal variability and should be considered in future studies.